Geminicoccus flavidas sp. nov. and Geminicoccus harenae sp. nov., two IAA-producing novel rare bacterial species inhabiting desert biological soil crusts - Jiang, Zhu-Ming; Deng, Yang; Han, Xue-Fei; Su, Jing; Wang, Hao; Yu, Li-Yan; Zhang, Yu-Qin (Frontiers in Microbiology, 2022)
Two Gram-stain negative strains (PCC 101082T and CPCC 101083T) isolated from biological sandy soil crusts samples collected from Badain Jaran desert, China. Both isolates were heterotrophic phototroph, could produce indole-3-acetic acid. The 16S rRNA gene sequences of these two strains were closely related to the members of the family Geminicoccaceae, showing high similarities with Geminicoccus roseus DSM 18922T (~ 96.9 %) and Arboricoccus pini B29T1T (~ 90.1 %), respectively. In phylogenetic tree based on 16S rRNA gene sequences, strain CPCC 101082T and CPCC 101083T formed a robust distinct clade with Geminicoccus roseus DSM 18922T within the family Geminicoccaceae, which indicated that these two isolates could be classified into the genus Geminicoccus. The growth of strain CPCC 101082T occurred at 15-42 °C and pH 4.0-10.0 (optima at 28-37 °C and pH 6.0-8.0). The growth of strain CPCC 101083T occurred at 4-45 °C and pH 4.0-10.0 (optima at 25-30 °C and pH 6.0-8.0). The major cellular fatty acids of CPCC 101082T and CPCC 101083T contained C18:1ω7c/C18:1ω6c, cyclo-C19:0ω8c and C16:0. Q-10 was detected as the sole respiratory quinone. Diphosphatidylglycerol, phosphatidylglycerol, phosphatidylcholine, phosphatidylethanolamine, an unidentified phospholipid and an unidentified aminolipid were tested in the polar lipids profile. The genomes of the two isolates were characterized as about 5.9 Mbp in size with the G+C content of nearly 68 %. The IAA-producing encoding genes were predicated in both genomes. The values of average nucleotide identity were 80.6 %, 81.2 % and 92.4 % based on a pairwise comparison of the genomes of strains CPCC 101082T and CPCC 101083T and Geminicoccus roseus DSM 18922T, respectively. On the basis of the genotypic, chemotaxonomic and phenotypic characteristics, the strains CPCC 101082T (=NBRC 113513T =KCTC 62853T) and CPCC 101083T (=NBRC 113514T =KCTC 62854T) are proposed to represent two novel species of the genus Geminicoccus with the names Geminicoccus flavidas sp. nov. and Geminicoccus harenae sp. nov..